Effects of seeking compensation on the psychological health and recovery of injured patients: the role of stress vulnerability and injury-related disability. Issue 1 (9th January 2022) - Pozzato, I.; Kifley, A.; Craig, A.; Gopinath, B.; Tran, Y.; Jagnoor, J.; Cameron, I. D.
Abstract: Background: Seeking compensation has been shown to have an adverse effect on the psychological health and recovery of injured patients, however, this effect requires clarification. Methods: A total of 2019 adults sustaining a traffic injury were recruited. Of these, 709 (35.1%) lodged a compensation claim. Interviews occurred at 1-, 6- and 12-month post-injury. Outcomes were psychological distress (posttraumatic stress (PTS) and depressive symptoms) and health-related functioning (HrF) (quality of life measured by EQ-5D-3L and disability by WHODAS) over 12-months post-injury. Covariates included individual stress vulnerability (preinjury, injury-related factors). Results: Compared with non-compensation participants, compensation groups had higher stress vulnerability (more severe injuries and negative reactions) and poorer baseline outcomes (psychological health and HrF). After adjustment, we found an effect of compensation on HrF [ β -0.09 (−0.11 to −0.07), p < 0.001] and PTS [ β = 0.36 (0.16 to 0.56), p = 0.0003], but not on depression [ β = −0.07 (−0.42 to 0.28), p = 0.7]. Both groups improved over time. Vulnerable individuals ( β = 1.23, p < 0.001) and those with poorer baseline outcomes (PTS: β = 0.06, p = 0.002; HrF: β = −1.07, p < 0.001) were more likely to lodge a claim. In turn, higher stress vulnerability, poor baseline outcomes and claiming compensation were associated with long-term psychological distress and HrF. Nevertheless, concurrent HrF in the model fully accounted for the compensation effect on psychological distress ( β = −0.14, p = 0.27), but not vice versa. Conclusions: This study provides convincing evidence that seeking compensation is not necessarily harmful to psychological health. The person's stress vulnerability and injury-related disability emerge as major risk factors of long-term psychological distress, requiring a whole-systems approach to address the problem.